Species composition, abundance, size distribution, sex ratios, and movement of Scylla mud crabs within the mangrove ecosystem at Setiu Wetland, Terengganu, Malaysia - Hanafiah Fazhan; Mohamad N. Azra; Siti Aisah Halim; Muhamad Naimullah; Muyassar H. Abualreesh; Alexander Chong Shu-Chien; Youji Wang; Yushinta Fujaya; Mohammad Syahnon; Hongyu Ma; Khor Waiho; Mhd Ikhwanuddin (Frontiers in Marine Science, 2022)
The aim of the present study was to determine the movement patterns of mud crabs, genus Scylla , within the mangrove area of the Setiu Wetland in Terengganu, Malaysia. Mark-release-recapture technique were conducted during 24 sampling trips. A fluorescent visible implant elastomer (VIE) tag was inserted within the crab’s shell and they were released at the same capture stations over an interval of two weeks before the next sampling. A total of 288 crabs of various sizes, sex and species were identified, measured, tagged and recorded. The numbers of male crabs were higher than females. Three species were present, dominated by S. olivacea at 54.2% and S.tranquebarica at 26.4%, with S. paramamosain in third place at 19.4%. Among the 288 crabs that were tagged and released, 26.38% were recaptured. The tagged crabs did not move very far from the release station based on the recapture data. The greatest mean chance of being recaptured within 24 h was 44.5%, and there were no tagged crabs recaptured after 48 h even on sampling trips at several points from the release site. Knowledge of movement patterns is essential to understand migration and population dynamics and the relationship between reproduction and local distribution.